Legal Protection of Children in Media Reporting Through the Implementation of Child-Friendly News Guidelines - Padang, Melisa Junita; Esther, July (Manunggal Halim Jaya, 2025)
This study examines legal protection efforts for children in media reporting through the implementation of Child-Friendly Reporting Guidelines (PPRA). The mass media has a strategic role in conveying information to the public but is also responsible for protecting children's rights, privacy, and dignity. Children who are the subjects of the news, either as victims or witnesses, often face the risk of exploitation and privacy violations, especially in sensational reporting. This article aims to encourage the press community to produce news that has a positive nuance and is oriented towards protecting the identity and rights of children in order to minimize the negative impact of reporting. The study uses normative legal methods to analyze relevant journalistic regulations and codes of ethics. The results of the analysis show that implementing PPRA is an important legal and ethical instrument to maintain a balance between press freedom and child protection while encouraging more responsible journalistic practices.